1999
DOI: 10.1136/adc.80.3.257
|View full text |Cite
|
Sign up to set email alerts
|

A search for the evidence supporting community paediatric practice

Abstract: Aim-Controversy exists regarding the evidence base of medicine. Estimates range from 20% to 80% in various specialties, but there have been no studies in paediatrics. The aim of this study was to ascertain the evidence base for community paediatrics. Methods-Twelve community paediatricians working in clinics and schools in Yorkshire, Manchester, Teesside, and Cheshire carried out a prospective review of consecutive clinical contacts. Evidence for diagnostic processes, prescribing, referrals, counselling/advice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Whereas publication of adult randomised clinical trials (RCTs) increased by 4.71/year between 1985 and 2004, publication of paediatric RCTs increased by 0.4/year 2. In one study of community paediatric practice, only 40% of clinical decisions involving children were found to be evidence-based or supported by good-quality trials 3. Moreover, most paediatric studies were found to suffer from small sample sizes, which make them less likely to detect important treatment effects 1…”
Section: Introductionmentioning
confidence: 99%
“…Whereas publication of adult randomised clinical trials (RCTs) increased by 4.71/year between 1985 and 2004, publication of paediatric RCTs increased by 0.4/year 2. In one study of community paediatric practice, only 40% of clinical decisions involving children were found to be evidence-based or supported by good-quality trials 3. Moreover, most paediatric studies were found to suffer from small sample sizes, which make them less likely to detect important treatment effects 1…”
Section: Introductionmentioning
confidence: 99%
“…evidence-based medicine. Only a subgroup of children receives treatments approved for pediatric use (1)(2)(3). Prevalence of adverse drug reactions to off-label medication are high (4), because doses are estimated by body weight (5)(6)(7) under the assumption that children are small adults.…”
Section: Introductionmentioning
confidence: 99%
“…Predictably, these difficulties may deter researchers and funding bodies and may have contributed to the dearth of high-quality paediatric research (4,5). As a result, <40% of paediatric medical decisions are supported by sufficient evidence (6), and most of these decisions are based on the results of research conducted with adult populations or no research whatsoever (7)(8)(9)(10).…”
mentioning
confidence: 99%